The glutamate dehydrogenase of the slow growing mycobacteria : its function in nitrogen metabolism and importance to in vitro and intracellular survival - Viljoen, Albertus Johannes (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.